Early Palaeozoic subduction-accretion in East Junggar (NW China): Insights from age, geochemical, and Sr-Nd-Hf isotopic data of andesitic rocks in the northern Yemaquan Arc - An, Rui; Zhao, Guochun; Liu, Qian; Han, Yigui (Lithos, 2021)
East Junggar is a key element of the southwestern Central Asian Orogenic Belt and the subject of debate relating to the initiation of accretion during the early Palaeozoic. We present zircon UPb ages, geochemistry and Sr–Nd–Hf isotopic compositions of early Palaeozoic andesitic rocks from the Kayishekuola area, northern East Junggar, NW China. The volcanic rocks consist of andesites and basaltic andesites, which yielded zircon UPb ages of 466–422 Ma. Andesites with ages of ca. 466 Ma were probably part of the earliest magmatic arc within northern East Junggar. These andesitic rocks are medium-K and calc-alkaline, with high SiO2 (55.02–58.59 wt%), Na2O + K2O (3.86–5.63 wt%), and Al2O3 (16.04–17.01 wt%) contents. They are enriched in the large-ion-lithophile elements and depleted in Nb, Ta, and Ti, consistent with an arc origin related to subduction of the Paleo-Asian Ocean. They have positive whole-rock εNd(t) and zircon εHf(t) values (3.8–4.3 and 9.7–15.3, respectively). These features are consistent with production of primary magmas by partial melting of depleted mantle modified by subduction. Based on these data, we infer that the Yemaquan arc formed from island arc-related rocks from ca. 466 Ma and records advancing subduction and associated crustal growth during the early Palaeozoic, and retreating subduction during the Early Devonian. [Display omitted] •The 466 Ma andesites probably recorded the earliest magmatic arc event in East Junggar.•The 466–422 Ma mantle-derived andesites formed in an oceanic island arc setting.•Subduction beneath East Junggar advanced from 466 to 422 Ma.•Retreating subduction beneath East Junggar occurred during the Early Devonian.